Microstructure and deuterium retention of beryllium co-deposition layer formed under high density plasma exposure. (August 2017) - Miyamoto, Mitsutaka; Nishijima, Daisuke; Baldwin, Matthew J.; Doerner, Russell P.; Sagara, Akio
Highlights: A systematic study of the temperature effect on the microstructure and the deuterium retention property in beryllium co-deposition layers has been carried out using W samples exposed to D + Be and D + Be + He mixture plasmas in PISCES-B. The deposition layer formed on the sample exposed to D + Be plasma at 373 K mainly consists of polycrystalline hcp metallic Be with a grain size of about 10–20 nm, and He seeding to the mixture plasmas causes amorphization of the layer. The columnar structure consisting of Be2 C due to crystal growth appeared at high temperature exposure cases of > 773 K both with and without He seeding. The formation of these deposition layers brought about a significant D retention. Abstract: A systematic study of the temperature effect on the microstructure and the deuterium retention property in beryllium co-deposition layers has been carried out using W samples exposed to D + Be and D + Be + He mixture plasmas in the linear divertor plasma simulator PISCES-B. A deposition layer consisting of small grains of ∼10 nm with original hexagonal close-packed structure of beryllium was formed on a sample exposed to D + Be mixture plasmas at low temperature of 373 K. He seeding to the mixture plasmas was found to cause amorphization of the layer. In contrast, columnar structure consisting of Be2 C due to crystal growth appeared at high temperature exposure cases of > 773 K both with and without He seeding. The formation of these deposition layers brought about a significant D retention. Assuming all retained D atoms uniformly distribute within the deposition layers, the D/Be ratios are estimated to be about 0.05 for the low temperature exposure case of 573 K, and to be about 0.01 even for the high temperature at 773 K. In addition, post-irradiation of 3 keV-D2 + for Be deposited sample demonstrated that the hydrogen isotope retention behavior can be modified drastically, once the Be deposition layer is formed.